Multimodal assessment of the left ventricular ejection fraction by echocardiography, cardiac computed tomography and cardiac magnetic resonance in patients after SARS-CoV2 infection - Gać, Paweł; Wysocki, Andrzej; Beck, Ewelina; Poręba, Małgorzata; Poręba, Rafał (Frontiers in Physiology, 2025)
ObjectiveThe aim of the study was to compare the assessment of left ventricular ejection fraction (LVEF) performed using echocardiography, cardiac computed tomography (CCT) and cardiac magnetic resonance (CMR) in patients after SARS-CoV2 infection.Material and methodsThe study group consisted of 108 patients (54.17 ± 8.11 years, 52% women and 48% men) with a history of SARS-CoV-2 infection. In all patients, echocardiography, CCT and CMR examinations were performed based on the guidelines of scientific societies. In echocardiography, LVEF (LVEFECHO) was determined from the apical 4-chamber and 2-chamber views, with the biplane Simpson’s method. In CCT, LVEF was assessed based on the contours of the left ventricular endocardium and epicardium in multiplanar reconstructions (MPR) from the multiphase of the entire cardiac cycle, which was part of the protocol of coronary computed tomography angiography performed with retrospective ECG gating with radiation dose modulation (LVEFCCT1). Additionally, in CCT, LVEF was assessed based on the left ventricular blood pool in the above reconstructions (LVEFCCT2). For the assessment of LVEF in CMR (LVEFCMR), a standard volumetric method was used using CINE sequence images in the 2-chamber projection in the long axis and in the short axis of the left ventricle. The coefficient of variation of measurements (CV) was calculated for each pair of LVEF measurements, as well as for all LVEF measurements.ResultsThe mean LVEF measurement values in the study group were 59.72% ± 7.39% for LVEFECHO, 63.36% ± 9.32% for LVEFCCT1, 64.5% ± 9.79% for LVEFCCT2, and 60.84% ± 9.29% for LVEFCMR. LVEFECHO was statistically significantly lower than LVEFCCT1 and LVEFCCT2. LVEFCMR was also statistically significantly lower than LVEFCCT1 and LVEFCCT2. CV for all LVEF measurements was 4.61% ± 1.73%. When comparing pairs of LVEF measurements, the lowest CV was observed for LVEFCCT1 and LVEFCCT2 (2.97% ± 2.64%), while the highest CV was observed for LVEFECHO and LVEFCCT2 (6.04% ± 3.39%). When comparing LVEF to the gold standard of assessment, i.e., LVEFCMR, the most consistent measurements were obtained for LVEFECHO (CV 3.00% ± 2.01%), while the least consistent measurements were obtained for CCT2 (4.65% ± 3.24%). A positive correlation was found between body mass index and CV of LVEF measurements (r = 0.44, p < 0.05), as well as between heart rate (during CCT) and CV of LVEF measurements (r = 0.37, p < 0.05). Furthermore, a negative correlation existed between LVEF measured by ECHO and CV of LVEF measurements in this group of patients (r = - 0.27, p < 0.05).ConclusionThere are statistically significant differences in left ventricular ejection fraction measurements in patients with a history of SARS-CoV-2 infection using different cardiac imaging modalities. Cardiac computed tomography overestimates LVEF compared to echocardiography and cardiac magnetic resonance imaging. Patients with abnormal body mass, suboptimal heart rate and reduced left ventricular systolic function are subgroups with increased variability of LVEF measurements in different cardiac imaging modalities.